Penanganan Orang dengan Gangguan Jiwa Terlantar Perspektif Siyasah Tanfidziyyah - Riski Ferdiansyah Ridwan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the implementation of Article 77 paragraph (1) letter d of Law Number 17 of 2023 on Health in handling neglected persons with mental disorders (ODGJ) in Bandar Lampung City and to examine it from the perspective of Siyasah Tanfidziyyah. This research employs a qualitative method with an empirical approach through interviews, documentation and literature review. The results show that policy implementation has been carried out through outreach, assessment, referral to health services and social rehabilitation; however, it has not been optimal due to limited facilities, administrative constraints related to identity and weak cross-sectoral coordination. This condition gives rise to legal implications in the form of the unfulfilled right to health services and social welfare, as well as indicating a gap between legal norms and their implementation. From the perspective of Siyasah Tanfidziyyah, this reflects the suboptimal execution of government responsibility in ensuring public welfare and protecting vulnerable groups, thus requiring the strengthening of policies and institutional capacity.